2017
DOI: 10.2337/db17-0364
|View full text |Cite
|
Sign up to set email alerts
|

GATA6 Controls Insulin Biosynthesis and Secretion in Adult β-Cells

Abstract: GATA4 and GATA6 play essential, but redundant, roles in pancreas formation in mice, and mutations cause pancreatic agenesis in humans. mutations have also recently been linked to adult-onset diabetes, with subclinical or no exocrine insufficiency, suggesting an important role for GATA6 in human β-cell physiology. To investigate the role of GATA6 in the adult endocrine pancreas, we generated mice in which is specifically inactivated in the pancreas. These mice develop glucose intolerance. Islets deficient in GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 42 publications
(47 reference statements)
3
26
0
3
Order By: Relevance
“…Importantly, the expression of key transcriptional regulators of adult ß cell function such as Pdx1 , MafA , and Nkx6.1 was also diminished. Similar to what it is observed during pancreas embryonic development, GATA6 directly regulates the expression of Pdx1 in adult ß cells . Thus, the effects of GATA6 loss on adult ß cell function might be indirect.…”
Section: Role Of Gata Factors In Mouse Pancreas Formationsupporting
confidence: 62%
See 3 more Smart Citations
“…Importantly, the expression of key transcriptional regulators of adult ß cell function such as Pdx1 , MafA , and Nkx6.1 was also diminished. Similar to what it is observed during pancreas embryonic development, GATA6 directly regulates the expression of Pdx1 in adult ß cells . Thus, the effects of GATA6 loss on adult ß cell function might be indirect.…”
Section: Role Of Gata Factors In Mouse Pancreas Formationsupporting
confidence: 62%
“…A recent study in Gata6 ‐deficient mice has demonstrated an important role for GATA6 in ß cell development and function. In this study, Gata6 was inactivated during early pancreas development using the mouse Pdx1‐Cre line . No pancreatic endocrine defects were observed in young Gata6 ‐deficient mice.…”
Section: Role Of Gata Factors In Mouse Pancreas Formationmentioning
confidence: 93%
See 2 more Smart Citations
“…The ability to explain additional clinical abnormalities that are associated with the underlying genetic cause is one of the major benefits of precision medicine. One such example is cardiac defects in patients with GATA6 mutations and remission of transient diabetes in patients with 6q24 methylation abnormalities [54]. …”
Section: Monogenic Diabetes: the Field Where Precision Diabetes Has Amentioning
confidence: 99%